Atomisation of nanometre-scaled jasmine flower extracts using electrospray method - S., Rahmam; M. N., Naim; N. F. A., Bakar; M. N., Mokhtar (Faculty of Food Science Technology, Universiti Putra Malaysia, 2022)
The present work demonstrated the application of a non-thermal technique to solidify nanometre-scaled atomised droplet using electrostatic atomiser or electrospray. The droplets were prepared in an aqueous solution, and consisted of bioactive compounds extracted from jasmine flower. The jasmine flower extracts were electrosprayed at various concentrations of 5, 15, and 25 wt%, with the working distances between the needle’s tip to an aluminium collector being 10, 20, and 30 cm. During the process, the water evaporation rate decreased from 2.02 to 1.02 nm3/s when the distance was increased from 10 to 30 cm at 5 wt% concentration. The same decreasing evaporation rate pattern was also observed when the concentration was increased from 5 to 25 wt%. On the contrary, increasing droplet fission numbers were observed as the distance was increased from 10 to 30 cm (i.e., from 7 to 406 at 25 wt% concentration) due to the electrostatic charge increment per unit area as the water left the droplet surface. Therefore, water evaporation and droplet fission number are important for solidifying the compounds when the droplets have exceeded their Rayleigh limit.